Anti-solvatochromic fluorescence enhancement via the suppression of S1-T2 intersystem crossing by polarity - Hao Li; Juanjuan Zhang; Yue-Tong Fang; Yu-Min Wang; Gui-Yuan Wu; Zhenggang Lan; Zhou Lu (Next Materials)
Attenuated fluorescence of organic fluorescent probes is typically observed in hydrophilic environments due to solvatochromic fluorescence quenching, where the brightness decreases along with increasing solvent polarity. However, strategies to overcome this challenge remains elusive. Herein, we report polarity-facilitated anti-solvatochromic fluorescence enhancement, i.e., the emission becoming stronger in solvents with higher polarity, of two novel donor-acceptor type fluorescent probes. Using the femtosecond (nanosecond) UV/vis pump-broadband probe spectroscopy combined with density function theory calculations, we investigate the excited-state dynamics of these fluorescent probes as a function of solvent polarity. The femtosecond transient absorption spectra reveal an initial hypsochromic shift of the excited-state absorption signature, immediately after excitation, indicating rapid stabilization of the lowest excited state through dipole-dipole interactions. The gradual ground-state recovery is accompanied by the formation of a new persistive excited-state absorption signature suggesting the competition between fluorescent recombination and intersystem crossing (ISC). Our TDDFT calculations suggest that a rare S1-T2 intersystem crossing is inhibited by solvent polarity, prolonging the S1 lifetime and thereby preventing the solvatochromic fluorescence quenching. This study provides new insights into the ISC-mediated fluorescence enhancement, offering potentials for investigating polarity-sensitive chemical and biological processes.